Design and implementation of automated flexible multisource charging system for hybrid electric vehicles. (30th October 2009) - Rao, Gorantla Srinivasa; Rao, G.K.; Murthy, G.R.K.; Swathi, D.; , Y. Obulesu
The scarcity and cost of fossil fuels, combined with their greenhouse gas emissions, make the development of nonfossil fuel-based methods of transportation a high-priority task. This paper proposes the designing and sizing of a Multiple Input Hybrid Charging System (MIHCS) to be used in Hybrid Electric Vehicle (HEV) propulsion. It includes a fuel cell generator, solar cell charger, Internal Combustion Engine (ICE), flywheel storage system, on-board sources and a combined Energy Storage System (ESS) comprising a battery pack. Based on the speed range of the vehicle, multiple sources like solar energy, fuel cells and wind power are automatically selected for propulsion or charging purposes by using computer and interfacing circuits. To realise this logic, a program has been developed in 'C' language. This logic also helps in controlling the charging and discharging times of the batteries placed in the energy storage unit.